Bridging the Survival Gap: Strengthening Post‑Discharge Care for Preterm Infants in Tanzania - Erick Mahatara; Kelvin Musa; Beatrice Jerome; Linda Paul Athman (Annals of Global Health, 2026)
Background: Despite notable progress in inpatient neonatal care expansion in Tanzania, expanding from 14 facilities in 2018 to 362 by 2025, a critical survival gap persists during the post‑discharge transition. National policies heavily prioritize pre‑discharge mortality, leaving the high‑risk, 60‑day post‑discharge window unaddressed. This study evaluates targeted policy, financing, and digital health interventions designed to mitigate post‑discharge neonatal mortality. Methods: We analyzed integrated implementation pathways within the Tanzanian health sector, specifically examining the institutional feasibility, scaling capacity, and clinical outcomes of the NEST360 Implementation Tracker (NEST‑IT) and the Essential Coaching for Every Mother Tanzania (ECEM‑TZ) mobile health framework. Results: Implementation data demonstrate that NEST‑IT is a highly viable data‑surveillance tool, achieving a 93% feasibility rate for daily clinical use and providing real‑time data to drive national quality improvement targets. Concurrently, the ECEM‑TZ digital platform effectively circumvents nurse‑midwife resource limitations by providing a 54‑message educational framework that improves caregiver knowledge and triples postnatal check‑up attendance. Conclusion: Eliminating post‑discharge mortality requires expanding longitudinal care frameworks. To achieve Tanzania’s national target of 15 neonatal deaths per 1000 live births, strategic imperatives must include institutionalizing zero‑rated mHealth tools, formalizing community health worker follow‑up protocols, and explicitly integrating specialized outpatient neonatal services into the standard benefit package of the 2026 universal health insurance rollout.